Test the Antioxidant Effectiveness of Oyster Mushroom (Pleurotus ostreatus) Ethyl Acetate Fraction Cream Formula using FRAP (Ferric Reducing Antioxidant Power) and ABTS (2,2'-azino-bis (3-3) ethylbenzothiazoline-6-sulphonic acid) Methods) - Nadjamuddin, Mirfaidah; Auliah, Nielma; Mulyadin; Tajuddin, Zakiah; Andriawan, Riki (Jurnal Penelitian Pendidikan IPA, 2023)
Antioxidants are compounds that can fight the influence of free radical molecules due to chemical reactions and metabolic events in the body. Phenolic compounds work to reduce the reaction of increasing the oxidation number, and are able to reduce highly reactive free radicals, lipid peroxidation processes, and metal oxides that can be obtained from oyster mushrooms. This study aims to make an antioxidant cream preparation and measure the IC50 value by conducting an antioxidant test of the ethyl acetate fraction of oyster mushroom (Pleurotus ostreotus) cream using FRAP (ferric reducing antioxidant power) and ABTS (2.2'-azino-bis (3-3) ethylbenzothiazoline-6-sulphonic acid) methods. The methods used are FRAP and ABTS where oyster mushrooms go through a liquid-liquid partition process and are made into cream preparations with formula concentrations of 2%, 4% and 6%, then their antioxidant activity is seen. The results of measuring three cream formulas obtained an IC50 value using the FRAP method of 110.12 bpj, and an IC50 value using the ABTS method of 84.61 bpj. The conclusion was that the IC50 value using the FRAP method (110.12 bpj) had medium category activity and the IC50 value using the ABTS method (84.61 bpj) had strong category activity.